2004
DOI: 10.1038/sj.ijo.0802760
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbohydrate overfeeding on whole body macronutrient metabolism and expression of lipogenic enzymes in adipose tissue of lean and overweight humans

Abstract: OBJECTIVE: Lipids stored in adipose tissue can originate from dietary lipids or from de novo lipogenesis (DNL) from carbohydrates. Whether DNL is abnormal in adipose tissue of overweight individuals remains unknown. The present study was undertaken to assess the effect of carbohydrate overfeeding on glucose-induced whole body DNL and adipose tissue lipogenic gene expression in lean and overweight humans. DESIGN: Prospective, cross-over study. SUBJECTS AND METHODS: A total of 11 lean (five male, six female, mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
66
1
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 31 publications
6
66
1
5
Order By: Relevance
“…Taking into account the fact that lipogenesis is a process that leads to lipid synthesis (lipogenesis ''de novo,'') our results suggest that the consumption of highfat diets such as HSFA and HMUFA diets do not activate the ''de novo'' synthesis of lipids in MetS patients. This is in contrast to what was observed for the consumption of a low-fat high-complex carbohydrate diet, which seems to activate lipogenesis in adipocytes, as previously reported in a healthy, overweight population (Minehira et al 2004).…”
Section: Discussioncontrasting
confidence: 99%
“…Taking into account the fact that lipogenesis is a process that leads to lipid synthesis (lipogenesis ''de novo,'') our results suggest that the consumption of highfat diets such as HSFA and HMUFA diets do not activate the ''de novo'' synthesis of lipids in MetS patients. This is in contrast to what was observed for the consumption of a low-fat high-complex carbohydrate diet, which seems to activate lipogenesis in adipocytes, as previously reported in a healthy, overweight population (Minehira et al 2004).…”
Section: Discussioncontrasting
confidence: 99%
“…This is in agreement with previous studies where lower expression of FASN was seen in adipose tissue of obese individuals, despite this group having increased hepatic lipogenesis compared with the lean [13], and where lower expression of FASN was seen in adipose tissue of obese individuals irrespectively of diet [35]. Other studies have not found any clear evidence that DNL is more active in adipose tissue obtained from obese individuals [36], even following a high carbohydrate diet [12]. In contrast to our findings, Berndt et al [14] recently found increased FASN expression in the adipose tissue of obese compared with lean individuals.…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, it is clear that DNL does operate in human adipose tissue [10,11], although it is not the major pathway for fat deposition. Expression of several lipogenic genes, principally FASN, has been shown to be higher in smaller human adipocytes [12,13]. Recently, however, it has been proposed that increased energy intake and accumulation of body fat is linked to increased expression of the lipogenic gene FASN in adipose tissue [14].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the evidence that adipose tissue is a site of DNL may be derived from different observations: Note that in the study described above, 33 the fractional activity of the pentose-phosphate pathway failed to increase after CHO overfeeding.…”
Section: Do Obese Women Convert More Cho To Fat Than Lean Women?mentioning
confidence: 94%
“…In a more recent overfeeding study also performed in overweight subjects, whole-body net DNL was found to be lower than in normal subjects ( Figure 6). 33 One explanation for the lower value in overweight subjects is that their impaired suppression of plasma-free fatty acids observed after CHO loading may contribute to blunt net DNL, since it seems that fatty acids inhibit the expression of lipogenic enzymes. 33 This study concluded that whole-body net DNL is not increased in overweight individuals in the situation of positive energy balance induced by CHO overfeeding.…”
Section: Do Obese Women Convert More Cho To Fat Than Lean Women?mentioning
confidence: 99%